FROM INNOVATION TO RISK: STABLECOINS AND FINANCIAL STABILITY IN DIGITAL FINANCIAL INFRASTRUCTURE - MARTIN, Vesna (Journal of process management and new technologies, 2026)
Stable cryptocurrencies represent one of the most significant innovations in the field of digital finance. Their accelerated development and increasing representation in modern financial flows have raised numerous questions regarding their potential benefits, risks, and impact on financial stability. The goal of this work is to analyze the technological characteristics of stablecoins, assess their potential effects on financial stability, and review the regulatory approaches. The research is based on a qualitative approach, using the method of content analysis of relevant scientific and professional literature, regulatory documents, and market data, with the analysis of case studies of four representative models of stablecoins. Research results show that stablecoins can contribute to improving the efficiency of payment transactions, reducing transaction costs, strengthening financial inclusion, and modernizing the digital financial infrastructure. At the same time, their application can generate liquidity, operational, regulatory, and systemic risks that require adequate mechanisms of supervision and management. It is concluded that for the sustainable development of the market of stablecoins, it is necessary to establish a balance between encouraging technological innovations, transparent management of reserves, and the application of a comprehensive regulatory framework that will contribute to the preservation of financial stability.